THE ROLE OF THE BOSNIA AND HERZEGOVINA IN PROVIDING ASSISTANCE TO THE REPUBLIC OF TURKEY AFTER THE 2023 EARTHQUAKE (Security Dialogues, 2023)
A powerful earthquake of magnitude 7.8 hit Turkey and Syria on February 6,2023. Another strong earthquake occurred during the day and ground shook during theweek. Many buildings have been demolished and the search for residents is intense. Afterone week 31,643 deaths were confirmed. Turkey has officially sent a request for emergencyassistance through the Civil protection mechanisms of the European union, NATO, and theUN. Numerous countries have sent their rescue teams to Turkey, but also sent the necessarygoods for the survivors. Bosnia and Herzegovina joined in responding to the disaster in Turkey. Complex political structure and organization of agencies for responding to natural and otherdisasters in Bosnia and Herzegovina are difficult for providing aid to other countries. Despite this, rescue teams from Bosnia and Herzegovina went to Turkey. Members of the Mountainrescue service was the first to go to Turkey and were later joined by members of ArmedForces of Bosnia and Herzegovina. Significant funds and goods were collected in Bosnia andHerzegovina and transported to Turkey. Media reports state that the teams from Bosnia andHerzegovina have rescued many victims from the ruins. It is necessary to do engagementanalysis of rescue teams from Bosnia and Herzegovina and check the possibilities for fasterinvolvement in responding to natural and other disasters.
Keywords: Bosnia and Herzegovina, Turkey, emergency assistance, earthquake